TECHNOLOGICAL MEASURES TO IMPROVE THE QUALITY OF BREAD AND BAKERY PRODUCTS - Rahimova Aziza Rashidovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The bakery industry has witnessed changes with the integration of technological innovations that have revolutionized the production of bread and bakery products. These advances not only improved the efficiency of cooking processes, but also increased the quality, taste and nutritional value of the finished products. In this article, we consider the technological activities that play a decisive role in improving the standards of bread and bakery products.